Diagnostic and Therapeutic Properties of Exosomes in Cardiac Fibrosis - Fan, Jiwen; Ren, Meng; He, Yuquan (Frontiers in Cell and Developmental Biology, 2022)
Cardiac fibrosis results from both the differentiation of cardiac fibroblasts and excessive accumulation of extracellular matrix (ECM), leading to myocardial stiffness and reduced compliance of the ventricular wall. The conversion of cardiac fibroblasts to myofibroblasts is the most important initiating step in the process of this pathological cardiac remodeling. It occurs during the progression of many cardiovascular diseases, adversely influencing both the clinical course and outcome of the disease. The pathogenesis is complex and there is no effective treatment. Exosomes are extracellular vesicles that mediate intercellular communication through delivering specific cargoes of functional nucleic acids and proteins derived from particular cell types. Recent studies have found that exosomes play an important role in the diagnosis and treatment of cardiac fibrosis, and is a potential biotherapeutics and drug delivery vectors for the treatment of cardiac fibrosis. The present review aimed to summarize the current knowledge of exosome-related mechanisms underlying cardiac fibrosis and to suggest potential therapy that could be used to treat the condition.